2016
DOI: 10.20892/j.issn.2095-3941.2016.0066
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 as a prognostic marker according to breast cancer molecular subtype

Abstract: Objective: Ki-67 plays an important function in cell division, but its exact role is still unknown. Moreover, few works regarding its overall function were published. The present study evaluated the clinical significance of Ki-67 index as a prognostic marker and predictor of recurrence in different molecular subtypes of breast cancer. The relationship of Ki-67 index with different clinicopathological factors was also analyzed. Methods: Ki-67 index was measured in 107 cases of primary breast cancer from 2010-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(125 citation statements)
references
References 34 publications
12
85
2
2
Order By: Relevance
“…Ki67 is commonly assessed as a biomarker for tumor aggressiveness, resistance to chemotherapy, and to validate the risk of residual disease by immunohistochemistry [30,31]. However, the correlation of Ki67 index with disease free survival has only been consistently shown in luminal A breast cancers [32]. In this study, we demonstrated that the reciprocal expression of AnxA6 and GRF2 is regulated by Ca 2+ influx dynamics and that semi-quantitative analysis of the ratio of GRF2:AnxA6 can be used to broadly delineate the complex spectrum of TNBCs into rapidly growing and invasive subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is commonly assessed as a biomarker for tumor aggressiveness, resistance to chemotherapy, and to validate the risk of residual disease by immunohistochemistry [30,31]. However, the correlation of Ki67 index with disease free survival has only been consistently shown in luminal A breast cancers [32]. In this study, we demonstrated that the reciprocal expression of AnxA6 and GRF2 is regulated by Ca 2+ influx dynamics and that semi-quantitative analysis of the ratio of GRF2:AnxA6 can be used to broadly delineate the complex spectrum of TNBCs into rapidly growing and invasive subsets.…”
Section: Discussionmentioning
confidence: 99%
“…This nuclear protein is expressed in all active phases of cell cycle, but not in quiescent or resting cells in the G0 and early G1 phase [ 30 , 31 ]. For this reason, Ki-67 could be used as prognostic biomarker and metastatic predictor in many type of human malignancies [ 32 34 ]. However, recent study reports that Ki-67 is responsible for cancer resistance to chemotherapeutic agents via maintaining the cancer stem cell niche [ 17 ], and suggests that Ki-67 is an attractive therapeutic target in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ki67 is a reliable prognostic marker in determining the number of tumor cells that are in the S phase of the cell cycle. Antigen Ki67 is seen as an independent prognostic factor in relation to tumor recurrence [ 46 , 47 ]. Factors underlying the relationship between PON1 and these antigens are, as yet, unknown.…”
Section: Discussionmentioning
confidence: 99%